Variabilité Temporelle Des Températures Annuelles Et Saisonnières Dans l’Est Algérien - Ahmed, Laala; Djamel, Alatou (European Scientific Journal, ESJ, 2016)
In this study, we tried to characterize the tendency of some thermal variables and their annual fluctuations over a period of 30 years (1982-2011). The results show a spatial and temporal variability of the anomaly to the minimum and maximum temperatures. Cold years represent a percentage ranging from 40 to 57% of the years studied, while hot are estimated at 63% for the years analyzed. Thus, the analysis of long series of minimum and maximum temperature reveals statistically significant trends which present spatial variability for annual and spatiotemporal temperatures to seasonal temperatures. An evolution of annual maximum temperatures to a warming has been recorded for the majority of the provinces of eastern Algeria with notable increases up to + 3°C/30years for the wilaya of Batna. However, the minimum temperatures have downward trends in the range of -1.5°C and - 2°C/30years respectively in Jijel and Setif and upward trends varying between 0.5 and 1.7 °C/30 years. After this study, calculates the thermal anomaly and mapping trends can create a regional picture of the evolution of the temperature in eastern Algeria that shows a significant warming of this region over the past decades especially for the wilaya of Batna. This study includes a reference to define strategies to adapt to thermal variability in eastern Algeria.